Diagnostic signs of functional readiness of weightlifters to compete - Хор’яков [Volodymyr Khoriakov] Володимир Анатолійович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Was determined diagnostic value of the neural indices of functional readiness to compete at the qualified weightlifters at various stages of preparation. The experiment involved 15 athletes qualified master of sports and 20 students of the same age who are not involved in sports. It is shown that raising tonus of nonspecific activation and improvement of functional state of the actuators function after a three-week training cycle does not affect the level of sports performance.Increase athletic performance after a 10-week training cycle due to lower levels of background activity, increasing the intensity and the rate of generation of excitation in the central nervous system. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>